2019
DOI: 10.3390/f10100872
|View full text |Cite
|
Sign up to set email alerts
|

Geographical Distribution and Environmental Correlates of Eleutherosides and Isofraxidin in Eleutherococcus senticosus from Natural Populations in Forests at Northeast China

Abstract: Non-wood forest products (NWFPs) derived from understory plants are attracting attention about sustainable forestry development. Geographical distribution and climate correlates of bioactive compounds are important to the regional management for the natural reserves of medical plants in forests. In this study, we collected Eleutherococcus senticosus individuals from 27 plots to map the special distribution of concentrations of eleutheroside B, eleutheroside E, and isofraxidin in forests of Northeast China. Com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 34 publications
1
22
0
Order By: Relevance
“…Although other physiological factors such as relative humidity and wind velocity may have had a close relationship with the change in temperature, their contributions to sad expression scores were covered by the gradient of latitude. Latitude gradients may generate an integrated impact on sad scores with a combination of several environmental factors [37,38]. Environmental factors had no contributions to the sad expression scores in our study, which concurs with earlier findings from a pilot investigation [29].…”
Section: Driving Forces From Environmental Factorssupporting
confidence: 92%
See 1 more Smart Citation
“…Although other physiological factors such as relative humidity and wind velocity may have had a close relationship with the change in temperature, their contributions to sad expression scores were covered by the gradient of latitude. Latitude gradients may generate an integrated impact on sad scores with a combination of several environmental factors [37,38]. Environmental factors had no contributions to the sad expression scores in our study, which concurs with earlier findings from a pilot investigation [29].…”
Section: Driving Forces From Environmental Factorssupporting
confidence: 92%
“…Weather records were derived from city-wide stations. Topographic gradients of longitude and latitude information was also recorded as parts of the potential driving forces because their gradients can be related to change in regional climates [37,38].…”
Section: Study Area and Data Sourcementioning
confidence: 99%
“…Many reports have shown that the secondary metabolites of medicinal plants from different areas are different [ 13 ]. At present, much of the research has focused on the impact of the external ecological environment on medicinal plants, such as temperature, rainfall, light, and so on [ 14 ]. However, the effect of the internal environment of medicinal plants has seldomly been studied.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, owing to their anti-inflammatory [7], anticoagulant [8], antioxidant [9], anticancer [4,10], hepatoprotective [11], antidiabetic [12], neuroprotective [13], anxiolytic [14], antidepressant [15], antibacterial [16], and cardioprotective [17] effects, researchers have focused their attention on the synthesis of coumarins derivatives in addition to their isolation and purification from natural entities [18]. As one of the most prominent hydroxy coumarins, 7-hydroxy-6,8-dimethoxy coumarin [isofraxidin, IF] along with other related lead compounds (Figure 1), such as 8-hydroxy-6,7-dimethoxycoumarin [ [19][20][21][22][23][24]. In this regard, IF has shown several biological and pharmacological activities including antioxidant [25], cardioprotective [26], weight loss [27], anti-osteoarthritis [28], antimalarial [29], and neuroprotective [30] effects, with promising anticancer and anti-inflammatory effects.…”
Section: Introductionmentioning
confidence: 99%
“…As one of the most prominent hydroxy coumarins, 7-hydroxy-6,8-dimethoxy coumarin [isofraxidin, IF] along with other related lead compounds ( Figure 1 ), such as 8-hydroxy-6,7-dimethoxycoumarin [fraxidin], 7, 8-dihydroxy-6-methoxycoumarin [fraxetin], 5, 6-dihydroxy-7-methoxycoumarin [isofraxetin], 6-hydroxy-5, 7-dimethoxycoumarin [fraxinol], and 7-hydroxy-6-methoxycoumarin 8-glucoside [fraxin] are natural-based multi-targets, isolated from several phytomedicines especially in Acantopanax, Achillea, Artemisia, and Fraxinus genera. IF and related compounds attenuate multiple destructive signaling mediators and therapeutic targets in some diseases [ 19 , 20 , 21 , 22 , 23 , 24 ]. In this regard, IF has shown several biological and pharmacological activities including antioxidant [ 25 ], cardioprotective [ 26 ], weight loss [ 27 ], anti-osteoarthritis [ 28 ], antimalarial [ 29 ], and neuroprotective [ 30 ] effects, with promising anticancer and anti-inflammatory effects.…”
Section: Introductionmentioning
confidence: 99%